Seismic-site Characteristics of the National Seismological Network using the spectral ratio method (HVSR) (Damascus University Journal for the basic sciences, 2022)
The characteristics of the local site have a strong influence on the intensity of the ground shaking, and it is one of the main reasons that cause human and economic losses. Therefore, studying the seismic site condition has become important for designing infrastructures that withstand seismic forces. The site response varies from one place to another according to the  geological and hydrological settings as well as the properties of seism tectonic source including; earthquake magnitude and the path of seismic waves to the monitoring station. In the literature, there are many methods for estimating site response, including numerical (geotechnical), and experimental (spectral ratio and Fourier spectrum) techniques.In this study, 56 earthquakes were analyzed which were recorded in the National Seismological stations in 24 stations. To perform the analysis, earthquakes with magnitude greater than 3 and which took place during the years: 2009, 2010 and 2011were selected. Consequently, spectral ratio HVSR curves were obtained and the predominant period of soil (T0) and amplification (A0) were determined for each station site. Later on, the results were compared with the Nakamura method that applied on ambient noise portion of the actual earthquake signal. The estimated values are close to each other using the two methods of analysis for 10 stations, while they differ for the other 14 stations. The results indicate that this compatibility is greater in rocky sites where the variation in the acoustic impedance is great. The design response curves have been drawn using the information contained in the Syrian anti-seismic code 2012 and the results of this study. Comparing the inferred response curve in the code shows differences in the values and agreement in the period width (T0 and Ts). Calculated amplification ranges from 1.12 to 2.36, while the predominant period is between 0.35 and 0.68 seconds. It was noted that the majority of stations-sites have a classification of B or C, and this is suitable for the deployment of seismological stations. The results of this study are of great importance in terms of supplementing the data of the National Seismological Network with the necessary information, and considering that the inferred response curves represent rocky reference curves for the sites of the main cities in Syria for further future studies.
Keywords: site response; spectral ratio h/v; amplification; predominant period factor; Design response curve